2006
DOI: 10.1159/000093638
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Cys329Gly Mutation Causing Hereditary Factor VII Deficiency

Abstract: We have previously reported a homozygous Cys329Gly mutation in a Chinese patient with factor VII (FVII) deficiency. Others have found a heterozygous Cys329Gly mutation in the F7 gene from patients of three different pedigrees. However, none of the reports included the expression and characterization of the mutant FVII in vitro. To investigate the effect of Cys329Gly on FVII function, we carried out transient transfections of baby hamster kidney cells (BHK-21) with a mutant FVII construct and compared the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Pedigrees with Cys329Gly 25,26 and Cys329Arg 27 mutations have been reported previously, in which the levels of FVII antigens were reduced in all patients, with even lower levels of FVII activity. In vitro studies indicated that Cys329Gly had little effect on the synthesis and secretion of FVII, although the coagulation activity of the mutant protein was almost undetectable 28 . Ser339 was another novel mutation site detected in proband 1, which resulted in a primary aliphatic hydroxy in the catalytic domain of FVII protein; thus, mutations in this site could affect the activity of FVII correspondingly.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Pedigrees with Cys329Gly 25,26 and Cys329Arg 27 mutations have been reported previously, in which the levels of FVII antigens were reduced in all patients, with even lower levels of FVII activity. In vitro studies indicated that Cys329Gly had little effect on the synthesis and secretion of FVII, although the coagulation activity of the mutant protein was almost undetectable 28 . Ser339 was another novel mutation site detected in proband 1, which resulted in a primary aliphatic hydroxy in the catalytic domain of FVII protein; thus, mutations in this site could affect the activity of FVII correspondingly.…”
Section: Discussionmentioning
confidence: 96%
“…In the meantime, SIFT-based investigations showed all three variants is functionally damaging, while the PolyPhen-2 software program indicated the alternation of Ser339 and Gly156 is probably damaging while the replacement by Ser84 is possibly damaging to the newly synthesized protein little effect on the synthesis and secretion of FVII, although the coagulation activity of the mutant protein was almost undetectable. 28 Ser339 was another novel mutation site detected in proband 1, which resulted in a primary aliphatic hydroxy in the catalytic domain of FVII protein; thus, mutations in this site could affect the activity of FVII correspondingly.…”
Section: Discussionmentioning
confidence: 99%
“…All the patients in these reports had decreased FVII antigen and much lower FVII activity compared to the level of the FVII antigen. An in vitro study, which was carried out to investigate the effect of Cys329Gly, showed that the mutation had little affection on the FVII synthesis and secretion while the coagulation activity of the mutated protein was almost undetectable [15].…”
Section: Discussionmentioning
confidence: 99%
“…The mutation occurs in the exon 5 of F7 gene and alters residue 91 in EGF2 (EGF-like 2) domain of the protein. The EGF-like and the serine protease domains are necessary for FVII and TF interaction [64] . Previous studies have also shown that EGF2 mutations dramatically impair FVII coagulant activity by affecting protein-protein interactions [18,54] .…”
Section: Spcd G420vmentioning
confidence: 99%